Physical parameters of contact binaries through 2-D and 3-D correlation diagrams - Gazeas, K. D. (2009)
Physical parameters of contact binaries are studied through 2-D and 3-D correlations among them. It is shown that the physical parameters (i.e. mass, radius and luminosity) are closely correlated with the orbital period and mass ratio in the 3-D domain. These correlations can be used as a quality check for the parameters in every given solution of a contact binary. The empirical laws, extracted out of these correlations, are a useful tool for a quick estimate of physical parameters for the numerous contact binaries found in global sky surveys.